If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c = 3.5n + 49 Reorder the terms: c = 49 + 3.5n Solving c = 49 + 3.5n Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Simplifying c = 49 + 3.5n
| 12(a-4)=6(a+2) | | 6.4+2.1(z-2)=8.2 | | 3+x(6)=36 | | 6+8+7= | | 1x-8=-6x-7 | | 5(7x+12)=270 | | 8-(2x-1)=5-3x | | 6/7(x-4)-31/7=-5 | | (2/x)-(7/12) | | 2x^3-9x^2+12x+1=0 | | 20w^2+w=20 | | p^5/p^-3/2 | | 0.5x-3.5=0.2x-15 | | -2/5w-1=15 | | X^5-5x^4-2x^3= | | 50x+60y=27000 | | 5(8x+4)=380 | | 3x-(2x+9x)= | | .65x=245 | | x+1.2=4 | | -2/7(-14) | | -4.9t^2+121t+262=0 | | .25x=4 | | 6(1+y)=5(5+y) | | 3/5=(x+2)/6 | | 3/4n+6=9 | | 8y^3(6y^4m^7)= | | 8(7x-2)=488 | | 45x+6=303 | | (x-12)/6=(x+7)/4 | | 5/(x-2)=-3/(x+7)+37/(x-2)(x+7) | | 94+6a=-3a |